2022
DOI: 10.31949/educatio.v8i1.1996
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kemampuan Penalaran Matematis Siswa SMP Pada Materi Teorema Phytagoras

Abstract: Penelitian ini merupakan penelitian deskriptif kualitatif yang bertujuan untuk menganalisis tingkat kemampuan penalaran siswa dalam menyelesaikan permasalahan pada materi teorema pythagoras dengan pengkategorian tingkat kemampuan penalaran matematis tinggi, sedang, dan rendah. Subjek penelitian adalah siswa kelas IX sebanyak 20 orang. Bentuk pengambilan data yaitu pemberian 5 butir soal tes tertulis pada subjek terpilih. Hasil penelitian ini menunjukan klasifikasi kemampuan penalaran matematis siswa diperoleh … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
1
1
2
Order By: Relevance
“…In line with Lesiana & Hiltrimartin (2020) that the average reasoning ability with 30 students as the subject is 63,867 with a fairly good category. This result is different from the study by Ramdan & Lessa Roesdiana (2022) which showed that the average reasoning ability test with 20 students was 20.63 in the very low category. This is because there are still many students who find it difficult to understand mathematical material and concepts, so many of them also have less than optimal results.…”
Section: Questioncontrasting
confidence: 96%
“…In line with Lesiana & Hiltrimartin (2020) that the average reasoning ability with 30 students as the subject is 63,867 with a fairly good category. This result is different from the study by Ramdan & Lessa Roesdiana (2022) which showed that the average reasoning ability test with 20 students was 20.63 in the very low category. This is because there are still many students who find it difficult to understand mathematical material and concepts, so many of them also have less than optimal results.…”
Section: Questioncontrasting
confidence: 96%
“…Social arithmetic is one of the most essential subjects for students to master (Dila & Zanthy, 2020;Nuraeni et al, 2020;Sari & Rahayu, 2018). Social arithmetic is a part of mathematics that discusses the calculations used by people in everyday life problems (Aziz & Hidayati, 2022;Inayah, 2018). This is done because students have trouble addressing social arithmetic problems (Bela et al, 2021;Yunia & Zanthy, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Kemampuan penalaran adalah salah satu kemampuan yang harus dikuasai dalam proses pembelajaran (Qomara, Ratnaningsih and Santika, 2022;Ramdan and Roesdiana, 2022;Ramdani, Setiani and Lukman, 2021;Magfirah et al, 2020)). Pentingnya kemampuan penalaran dinyatakan oleh National Council of Teachers of Mathematic dalam Afinadhita and Abadi (2022); dengan dirumuskannya lima dasar kemampuan yang harus dikuasai para siswa, yaitu kemampuan dalam memecahkan sebuah masalah (problem solving), kemampuan dalam berkomunikasi (communication), kemampuan dalam berkoneksi (connections), kemampuan dalam bernalar dan pembuktian (reasoning and proof), serta kemampuan dalam merepresentasi (representation).…”
Section: A Latar Belakangunclassified